Aerobic Exercise Training With Optimal Intensity Increases Cardiac Thermal Tolerance in Juvenile Rainbow Trout - Pettinau, Luca; Seppänen, Eila; Sikanen, Asko; Anttila, Katja (Frontiers in Marine Science, 2022)
Domestication and selective breeding for rapid-growth have impaired the cardiorespiratory system of salmonids, which might compromise their capacity to tolerate environmental stressors, such as heat waves. Exercise training by swimming has been proposed as a potential tool to enhance growth, cardiac function and disease resilience in farmed fish and thereby improves aquaculture production. However, whether exercise training could also improve cardiac robustness against heat waves, which are becoming more common and cause severe challenges to aquaculture, remains unknown. Here, we trained juvenile rainbow trout at three different training velocities: 0.06 m*s-1 (or 0.9 body lengths per second [bl*s-1]; control group), 0.11 m*s-1 (or 1.7 bl*s-1; medium speed group) and 0.17 m*s-1 (or 2.7 bl*s-1; high speed group) for 5 weeks, 6h per day, 5 days per week. Measuring maximal heart rate (fHmax) during acute warming, we demonstrated that training at 1.7 bl*s-1 was optimal in order to increase the temperature at which fHmax reached its peak (Tpeak) as well as the upper thermal tolerance of the cardiovascular function (arrhythmia temperature, TARR), up to 3.6°C as compared to the control fish. However, more intensive training did not provide similar improvement on thermal tolerance. Both training regimes enhanced the ventricular citrate synthase activity which may provide higher aerobic energy production capacity for ventricles. Further mechanistic studies are needed to understand the complex interactions between training intensities and changes in thermal tolerance. Although not conclusive on that point, our findings present a valid training programme for hatchery salmonids to increase their cardiac thermal tolerance and consequently probably also their capacity to tolerate heat waves, which has a direct application for aquaculture.